2022
DOI: 10.1007/s11120-021-00892-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of photosynthesis related pigments in light harvesting, photoprotection and enhancement of photosynthetic yield in planta

Abstract: Photosynthetic pigments are an integral and vital part of all photosynthetic machinery and are present in different types and abundances throughout the photosynthetic apparatus. Chlorophyll, carotenoids and phycobilins are the prime photosynthetic pigments which facilitate efficient light absorption in plants, algae, and cyanobacteria. The chlorophyll family plays a vital role in light harvesting by absorbing light at different wavelengths and allowing photosynthetic organisms to adapt to different environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(81 citation statements)
references
References 233 publications
6
75
0
Order By: Relevance
“…Tomato fruits also have no stomata on their surface [89,90]; however, work carried out by Tanaka et al [91], Hetheringon et al [92] and Obiadalla-Ali et al [93] in green developing tomato fruit showed that fruit contributed between 10% and 15% of the total fixed carbon of the fruit. Similar to the tomato, cherry fruit are green at the early stages of development and contain the necessary pigments to carry out photosynthesis (for a review of photosynthetic pigments and fruit photosynthesis, see [86,89,94,95]. These data suggest that the stomata on the surface of cherry fruit carry out a real physiological role, contributing carbon either directly by assimilating carbon from the atmosphere or through recycling photosynthesis, recapturing the CO 2 liberated by mitochondrial respiration.…”
Section: The Physiological Role Of Cherry Fruit Stomatamentioning
confidence: 99%
“…Tomato fruits also have no stomata on their surface [89,90]; however, work carried out by Tanaka et al [91], Hetheringon et al [92] and Obiadalla-Ali et al [93] in green developing tomato fruit showed that fruit contributed between 10% and 15% of the total fixed carbon of the fruit. Similar to the tomato, cherry fruit are green at the early stages of development and contain the necessary pigments to carry out photosynthesis (for a review of photosynthetic pigments and fruit photosynthesis, see [86,89,94,95]. These data suggest that the stomata on the surface of cherry fruit carry out a real physiological role, contributing carbon either directly by assimilating carbon from the atmosphere or through recycling photosynthesis, recapturing the CO 2 liberated by mitochondrial respiration.…”
Section: The Physiological Role Of Cherry Fruit Stomatamentioning
confidence: 99%
“…46 The xanthophyll cycle of higher plants is an important photoprotection mechanism during periods of high-light illumination. 47,48 In this context, the higher expression of VvZEP1 in the skin of grape berry at E-L 38 indicates that, in mature grapes, the epoxidation reaction mediated by the zeaxanthin epoxidase (ZEP) is favored over the enzymatic deepoxidation of violaxanthin to zeaxanthin, which corresponds with the observed higher amounts of 9-cis-violaxanthin measured in grape skin plastids at E-L 38. Thus, these findings provide clues that mechanisms of protection of the photosynthetic machinery are still important at the mature stage.…”
Section: Discussionmentioning
confidence: 76%
“…Carotenoids, as the second group of photosynthetic pigments, have antioxidant activity and participate in the protection of chlorophylls against photo-oxidative destruction. Carotenoids are divided into carotenes and oxygen-rich and oxygen-poor xanthophylls [ 48 , 49 ]. Photosynthetic pigments are necessary for the light phase of the photosynthesis process.…”
Section: Discussionmentioning
confidence: 99%